磷脂型DHA制备、检测及功能特性研究进展Preparation, detection and functional characteristics of DHA-phospholipid - 陈广琦1，贾敏2，宗爱珍2，徐同成2，苗颖1CHEN Guangqi1, JIA Min2, ZONG Aizhen2, XU Tongcheng2, MIAO Ying1 (Zhongguo youzhi, 2025)
磷脂型DHA因具有较高的DHA吸收率，近年来受到广泛关注。旨在为磷脂型DHA在功能性脂质产品中的应用提供参考，从磷脂型DHA的酶法制备方法、检测方法和功能特性等方面进行综述。酶法制备磷脂型DHA具有条件温和、安全性高等特点，主要分为酶催化酸解法、酶催化酯交换法和酶催化酯化法等。磷脂型DHA的检测方法有薄层色谱-气相色谱法、核磁共振法、高效液相色谱-串联质谱法等。磷脂型DHA具有抗癌、改善脂质代谢、抗炎和增强神经营养活性等功能特性。磷脂型DHA制备工艺的优化和检测方法的改进对于其在食品、医药等行业的应用具有重要意义。DHA-phospholipid (DHA-PL) has attracted much attention in recent years because of its high absorption rate of DHA. Aiming to provide reference for the application of DHA-PL in functional lipid products, the enzymatic preparation method, detection method and functional characteristics of DHA-PL were summarized. Enzymatic preparation of DHA-PL had the advantages of mild conditions and high safety, and mainly divided into enzyme catalytic acid hydrolysis method, enzyme catalytic transesterification method and enzyme catalytic esterification method. The methods for detecting DHA-PL include thin layer chromatography-gas chromatography, nuclear magnetic resonance, high performance liquid chromatography-tandem mass spectrometry, etc. DHA-PL has the functions of anticancer, improving lipid metabolism, anti-inflammatory and enhancing neurotrophic activity. Optimization of the preparation process and improvement of detection methods for DHA-PL is of great significance for the application of DHA-PL in industries such as food and pharmaceuticals.